Elaboramos pictograma con mi juguete favorito - Mendoza Quevedo, Elena Veronica (2018)
From the perspective of education, nowadays, the mathematics area is transformed into one of the essential bases for the cognitive and attitudinal development of students, especially primary level children, a necessary element for the solution of the diverse problematic situations that arise within their daily context. Likewise, the application of mathematical games favors the development of the capacities that are part of the mathematical task. And within these playful applications, we find the use of pictograms as a means to know, develop and apply statistical situations. And what better way to do this than with our children's favorite toys. Problem solving is understood as giving solutions to certain challenges, difficulties and obstacles that appear in the lives of children - remembering that they are always facing these situations, at home, at school and with the people around them. It is therefore necessary to know and apply the solution paths, organizing them adequately, so that they know when to use them.